2023
DOI: 10.1007/s11046-023-00741-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chronic Pulmonary Aspergillosis Co-infection on the Health-Related Quality of Life of Patients with Pulmonary Tuberculosis in Uganda

Abstract: BackgroundBoth pulmonary tuberculosis (PTB) and chronic pulmonary aspergillosis (CPA) signi cantly affect healthrelated quality of life (HR-QoL). We aimed to determine the impact of CPA co-infection on the HR-QoL of Ugandans with PTB. MethodsWe conducted a prospective study among participants with PTB with persistent pulmonary symptoms after 2 months of anti-TB treatment at Mulago Hospital, Kampala, Uganda between July 2020 and June 2021. HR-QoL was assessed using St. George Respiratory Questionnaire (SGRQ) at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Our recent study from Mulago Hospital (Kampala, Uganda) found that 32 (20%) of 162 patients with PTB who had persistent respiratory symptoms despite completing 2 months of TB treatment had CPA, 19 with patients with CPA-PTB co-infection having a much worse health-related quality of life at the time of TB treatment completion compared to those with PTB alone. 18 We reported death in a patient with CPA complicating PTB, with heart failure, 99 use of point of care lateral flow assay for Aspergillus specific immunoglobulin G and M (IgG/IgM) detection for early screening for CPA 100 and demonstrated that CPA is frequently misdiagnosed as PTB relapse among Ugandans with chronic respiratory symptoms following PTB treatment. 101 …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our recent study from Mulago Hospital (Kampala, Uganda) found that 32 (20%) of 162 patients with PTB who had persistent respiratory symptoms despite completing 2 months of TB treatment had CPA, 19 with patients with CPA-PTB co-infection having a much worse health-related quality of life at the time of TB treatment completion compared to those with PTB alone. 18 We reported death in a patient with CPA complicating PTB, with heart failure, 99 use of point of care lateral flow assay for Aspergillus specific immunoglobulin G and M (IgG/IgM) detection for early screening for CPA 100 and demonstrated that CPA is frequently misdiagnosed as PTB relapse among Ugandans with chronic respiratory symptoms following PTB treatment. 101 …”
Section: Discussionmentioning
confidence: 98%
“…Our recent work has shown that Ugandans with CPA-PTB co-infection have a poorer health-related quality of life compared to those with only PTB. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we were able to show that asthma and restrictive lung disease contributed to an additional 25% of participants with chronic respiratory symptoms. We have previously shown that chronic pulmonary aspergillosis (CPA) occurs in up to 20% of PTB patients with persistent symptoms (24), significantly affecting their quality of life during PTB treatment (25). Therefore, investigations for both infectious complications and ventilatory defects are indicated in patients with chronic respiratory symptoms following completion of PTB treatment.…”
Section: Discussionmentioning
confidence: 99%